Multicultural Islamic Cultural History Learning Strategies in Strengthening Religious Tolerance at Madrasah Aliyah Negeri 2 Yogyakarta - Tsaaniyatush Shoolihah Fauzan (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study examines the implementation of multicultural-based Islamic Cultural History (SKI) learning strategies in strengthening religious tolerance at Madrasah Aliyah Negeri 2 Yogyakarta. Using a descriptive qualitative approach, this research analyzes how SKI learning is designed and implemented to cultivate tolerant attitudes among students. The research findings indicate that the integration of multicultural values in SKI learning through dialogical discussion methods, historical case studies, and visits to diverse religious sites has proven effective in enhancing students' understanding and tolerance attitudes. Learning strategies that prioritize appreciation for diversity, contextual learning, and critical reflection are capable of shaping students' character to be inclusive and respectful of differences. This study recommends strengthening the multicultural-based SKI curriculum as an instrument of character education in madrasahs.